APANet: Auto-Path Aggregation for Future Instance Segmentation Prediction - Hu, Jian-Fang; Sun, Jiangxin; Lin, Zihang; Lai, Jianhuang; Zeng, Wenjun; Zheng, Wei-Shi (IEEE Transactions on Pattern Analysis and Machine Intelligence (TPAMI) (to appear), 2021)
.